Effect of facility-based HIV self-testing on uptake of testing among outpatients in Malawi: a cluster-randomised trial. Issue 2 (February 2020) - Dovel, Kathryn; Shaba, Frackson; Offorjebe, O Agatha; Balakasi, Kelvin; Nyirenda, Mike; Phiri, Khumbo; Gupta, Sundeep K; Wong, Vincent; Tseng, Chi-Hong; Nichols, Brooke E; Cele, Refiloe; Lungu, Eric; et al.
Summary: Background: HIV self-testing increases testing uptake in sub-Saharan Africa but scale-up is challenging because of resource constraints. We evaluated an HIV self-testing intervention integrated into high-burden outpatient departments in Malawi. Methods: In this cluster-randomised trial, we recruited participants aged 15 years or older from 15 outpatient departments at high-burden health facilities (including health centres, mission hospitals, and district hospitals) in central and southern Malawi. The trial was clustered at the health facility level. We used constrained randomisation to allocate each cluster (1:1:1) to one of the following groups: standard provider-initiated testing and counselling with no intervention (provider offered during consultations), optimised provider-initiated testing and counselling (with additional provider training and morning HIV testing), and facility-based HIV self-testing (Oraquick HIV self-test, group demonstration and distribution, and private spaces for interpretation and counselling). The primary outcome was the proportion of outpatients tested for HIV on the day of enrolment, measured through exit surveys with a sample of outpatients. Analyses were on an intention-to-treat basis. The trial is registered with ClinicalTrials.gov, NCT03271307, and Pan African Clinical Trials, PACTR201711002697316. Findings: Between Sept 12, 2017, and Feb 23, 2018, 5885 outpatients completed an exit survey—2097 in the HIV self-testing group, 1951 in the standard provider-initiated testing and counselling group, and 1837 in the optimised provider-initiated testing and counselling group. 1063 (51%) of 2097 patients in the HIV self-testing group had HIV testing on the same day as enrolment, compared with 248 (13%) of 1951 in the standard provider-initiated testing and counselling group and 261 (14%) of 1837 in the optimised provider-initiated testing and counselling group. The odds of same-day HIV testing were significantly higher in the facility-based HIV self-testing group compared with either standard provider-initiated testing and counselling (adjusted odds ratio 8·52, 95% CI 3·98–18·24) or optimised provider-initiated testing and counselling (6·29, 2·96–13·38). Around 4% of those tested in the standard provider-initiated testing and counselling and optimised provider-initiated testing and counselling groups felt coerced to test, and around 1% felt coerced to share test results. No coercion was reported in the facility-based HIV self-testing group. Interpretation: Facility-based HIV self-testing increased HIV testing among outpatients in Malawi, with a minimal risk of adverse events. Facility-based HIV self-testing should be considered for scale-up in settings with a high unmet need for HIV testing. Funding: United States Agency for International Development.